2011
DOI: 10.20460/jgsm.2011515804
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Efficiencies of Hospitals: An Application of Data Envelopment Analysis

Abstract: The aim of this study is to investigate the efficiencies of hospitals in Turkey with respect to their ownerships (i.e. state, education & research, university and private) for the years 2001 to 2006. The impact of health care reforms on the efficiencies is also examined in order to highlight possible policy implications for policy makers. Comparative performance evaluation of hospitals has been achieved by using Data Envelopment Analysis (DEA) as well as Malmquist Index calculations (i.e. to determine the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…Turkish researchers, with a similar tendency, carried out several DEA based efficiency studies in hospital services area. For instance, Ersoy et al (1997) firstly used DEA to measure efficiency of Turkish hospitals, Sezen & Gok (2011) assessed the efficiencies of Turkish hospitals regarding their ownership. Özgen Narcı et al (2015) studied the impact of competition on technical efficiency for the hospital industry.…”
Section: Dea Literaturementioning
confidence: 99%
“…Turkish researchers, with a similar tendency, carried out several DEA based efficiency studies in hospital services area. For instance, Ersoy et al (1997) firstly used DEA to measure efficiency of Turkish hospitals, Sezen & Gok (2011) assessed the efficiencies of Turkish hospitals regarding their ownership. Özgen Narcı et al (2015) studied the impact of competition on technical efficiency for the hospital industry.…”
Section: Dea Literaturementioning
confidence: 99%
“…In this context, Gok and Sezen (2011) state that one crucial way to increase the efficiency of the Turkish hospitals is by decreasing investments in the health field and/or increasing the production factors, such as the existing beds or physicians (Rezapoor et al, 2011). Moreover, Araújo and his colleagues (2014) argue that high investments in equipment and resources required to treat the patients can generate hospitals' inefficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that technical, managerial and scale e ciency of Iran hospitals after performing HSEP have decreased in comparison with before it. On the basis of a study on Turkey hospitals from 2001-2006, which measured the effect of Turkey health sector reform on hospitals e ciency to provide policy implications for policy makers, indicated that this reform has increased the e ciency of public hospitals but the e ciency of private hospitals has decreased [31].…”
Section: Table 5 Discussionmentioning
confidence: 99%